The Use of Census Geography and County Typologies in the Construction of Classification Systems for Rural Schools and Districts - William L. Ellder (Journal of Research in Rural Education, 1992)
I describe the characteristics of schools and school districts by interrelating NCES data using various Bureau of the Census and ERS county typologies. When rural school districts are defined as those where at least 75% of the students attend a school in a rural locale, then 47% of the nation's districts are rural and 53% are urban. Rural districts account for 22.3% of all regular public schools, 11.8% of all public school students, and 13.4% of teachers. Most of our 22,400 rural schools and 6.6 million rural students are in rural districts, but a sizable fraction are in urban districts as well. Differences in school size are discussed by region and county type. The analysis suggests that rural schools and rural districts are smallbecause theirpopulations are sparse and isolated, which makes the diseconomies of transportation to larger centers greater than the diseconomies of small scale. The prospects for more precise typologies of rural schools are considered in anticipation of forthcoming educational data based on the 1990 census Topologically Integrated Geographic Encoding Referencing (TIGER) files, which include levels of geographic detail not previously available for rural areas